2006
DOI: 10.1107/s0907444906016982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystal freezing and small-molecule binding on internal cavity size in a large protein: X-ray and docking studies of lipoxygenase at ambient and low temperature at 2.0 Å resolution

Abstract: Flash-freezing is a technique that is commonly used nowadays to collect diffraction data for X-ray structural analysis. It can affect both the crystal and molecular structure and the molecule's surface, as well as the internal cavities. X-ray structural data often serve as a template for the protein receptor in docking calculations. Thus, the size and shape of the binding site determines which small molecules could be found as potential ligands in silico, especially during high-throughput rigid docking. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…(2) Do the differences between molecular conformers exist in solution or are they the artifacts of flashfreezing? Meticulous studies of soybean LOX-3 at ambient and cryogenic conditions 35,36 showed the two molecules related in crystal by the 2-fold axis to lose that symmetry upon cooling when molecules were pushed several angstroms closer by the shrinking volume of the crystal. It has also been proven that rapid freezing of crystals not only can impact the conformation of the more flexible peripheral loops, but also can change the relative orientation of the molecules and, as a result, change the geometry of the crystal lattice and impact the size and shape of the internal cavity as well.…”
Section: Low-resolution (16 å) Structure In Solutionmentioning
confidence: 99%
“…(2) Do the differences between molecular conformers exist in solution or are they the artifacts of flashfreezing? Meticulous studies of soybean LOX-3 at ambient and cryogenic conditions 35,36 showed the two molecules related in crystal by the 2-fold axis to lose that symmetry upon cooling when molecules were pushed several angstroms closer by the shrinking volume of the crystal. It has also been proven that rapid freezing of crystals not only can impact the conformation of the more flexible peripheral loops, but also can change the relative orientation of the molecules and, as a result, change the geometry of the crystal lattice and impact the size and shape of the internal cavity as well.…”
Section: Low-resolution (16 å) Structure In Solutionmentioning
confidence: 99%
“…Also, rapid crystal freezing can affect not only crystal lattice but also molecules, especially external loops, hydrogen bonding network, and so on, even distribution of water in the cavities. 22 In this study, we first explored, by in silico modeling, possible associations of conformers (A The discrepancy factor χ indicates the difference between the experimental data and the fit of a linear combination of scattering profiles estimated from the monomer-dimer equilibrium as in the crystal structure and in the refined structure. The theoretical R g value calculated based on the crystal coordinates is 28.4 Å.…”
Section: Stability Of Lox Dimers In Aqueous Solutionsmentioning
confidence: 99%
“…It can be speculated that this molecular feature has been selected as an adaptation to lower water temperatures, in agreement with other studies on the thermo-adaptation of proteins to extreme environmental conditions. These molecules are usually characterised by a lower number of stabilizing factors compared to their counterparts from species living in more temperate environments and, therefore, by an higher flexibility [60][61][62]. Hovewer, our preliminary data [44] suggest that the structural differences between icefish IL-1 and sea bass and trout homologues are not linked to a different biological activity of this molecule as the regulation of icefish IL-1 after stimulation with lipopolysaccharide from E. coli and lectin from Phaseolus vulgaris Leucoagglutinin is comparable to other Teleosts.…”
Section: Discussionmentioning
confidence: 99%